Experimental and numerical analysis of non-contact magnetic detecting signal of girth welds on steel pipelines. (June 2022) - He, Guoxi; He, Tengjiao; Liao, Kexi; Deng, Shasha; Chen, Di
Abstract: The quality of the girth welds on pipelines is a critical point regarding the safe operation. Non-contact pipeline magnetic detection (NPMD) is a non-destructive detection technology based on the metal magnetic memory (MMM) method. However, present studies mostly focus on the qualitative analysis of girth welds instead of accurate quantitative analysis of the stress status. Here, many hydraulic tests in sealed pipelines are performed to investigate the magnetic signal under different internal pressures and detection heights. A numerical model of magnetic signal is established and verified by the experimental results. The results show the characteristics of the signal that the y component has sinusoidal fluctuations when the x and z component reach the extreme values. A new parameter K v s is proposed to comprehensively reflect the stress status of the girth welds. It is founded that the residual strength ratio ( RSR ) reduces from 0.97 to 0.83 when the K vs max increases from 7500 to 13500 nT/m The magnetic signals decay exponentially in the second order when the detection height varies within 0.1–1.0 m. This study provides a theoretical and experimental basis for identifying the stress status of the girth welds on pipelines. Highlights: Numerical field of non-contact magnetic signal is established and verified. Magnetic signal is influenced by stress at welds and detection height. The z component reaches the extreme valuesat girth welds. A parameter is proposed to reflect the stress status of the girth welds.